2009
DOI: 10.1007/s00520-009-0591-9
|View full text |Cite
|
Sign up to set email alerts
|

Hyperparathyroidism secondary to zoledronic acid infusion: case report

Abstract: Dear Editor, Bisphosphonates are analogs of inorganic pyrophosphate. They are potent inhibitors of osteoclast-mediated bone resorption, and are shown to be effective in reducing skeletal complications such as bone pain, pathologic fracture, bone surgery, and hypercalcemia [1][2][3][4][5]. Zoledronic acid is a new long-acting and highly potent biphosphonate. We report a patient who developed hyperparathyroidism secondary to zoledronic acid treatment.A 57-year-old female patient was referred to the hospital with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Interestingly, PTH remained signifi cantly increased by 90 % (range 20-252 %) 3 months after ZOL infusion and returned to baseline levels at 12 months, although calcium was normalized by the 10 th day in all patients ( Avramidis et al, 2008 ). This pattern of sustained PTH increase after BPs treatment, despite serum calcium normalization, has been also reported in other metabolic bone diseases including bone metastases ( Sayin and Yazici, 2009 ). Furthermore, there are 2 more case reports of severe, symptomatic hypocalcemia following BPs treatment in patients with PDB ( Stuckey et al, 2001 ;Whitson et al, 2006 ) and one in juvenile Paget's disease ( Polyzos et al, 2010 ).…”
Section: The Mode Of Bisphosphonate Action ▼supporting
confidence: 66%
See 1 more Smart Citation
“…Interestingly, PTH remained signifi cantly increased by 90 % (range 20-252 %) 3 months after ZOL infusion and returned to baseline levels at 12 months, although calcium was normalized by the 10 th day in all patients ( Avramidis et al, 2008 ). This pattern of sustained PTH increase after BPs treatment, despite serum calcium normalization, has been also reported in other metabolic bone diseases including bone metastases ( Sayin and Yazici, 2009 ). Furthermore, there are 2 more case reports of severe, symptomatic hypocalcemia following BPs treatment in patients with PDB ( Stuckey et al, 2001 ;Whitson et al, 2006 ) and one in juvenile Paget's disease ( Polyzos et al, 2010 ).…”
Section: The Mode Of Bisphosphonate Action ▼supporting
confidence: 66%
“…On the contrary, osteomalacia was not seen in bone biopsies of 2 patients who received high-dose PAM for PDB resistant to treatment ( Cundy et al, 1996 ). ( Sayin and Yazici, 2009 ) and bone loss following liver transplantation ( Crawford et al, 2006 ). Even in postmenopausal hemodialysis women, who had established secondary hyperparathyroidism, PAM infusion resulted in aggravation of hypocalcemia and secondary hyperparathyroidism ( Lu et al, 2003 ).…”
Section: The Mode Of Bisphosphonate Action ▼mentioning
confidence: 99%
“…Studies of denosumab 7,9,10 have shown that plasma PTH levels rise above the reference range (but tend to return to normal toward the end of the dose interval) in association with reduced albumin-adjusted calcium (which tends to remain in the reference range). Although there has been 1 case report of secondary normocalcemic hyperparathyroidism with zoledronate, 11 to our knowledge, there has been only 1 longitudinal study of the effect of a single dose of zoledronate on biochemical parameters, which found that PTH levels rose and calcium levels reduced following therapy; however, both remained within reference ranges. All previous studies have been longitudinal studies of postmenopausal women over a maximum of 12-month (for denosumab) or 24-month (for zoledronate) periods.…”
mentioning
confidence: 93%
“…
Dear Editor, We have read with interest the paper of Sayin and Yazici [1], describing a case of secondary hyperparathyroidism following multiple intravenous zoledronic acid (ZOL) infusions in a patient with stomach lymphoma and bone metastases. The authors supported that serum parathyroid hormone (PTH) continued to increase, despite serum calcium and vitamin D normalization, until ZOL infusions were stopped.

Hypocalcemia has been described after ZOL, as well as after other bisphosphonates (BPs), in various conditions, including bone metastases, Paget's disease of bone (PDB), and osteoporosis.

…”
mentioning
confidence: 97%